A new monsoon circulation index defining precipitation variability in the East Asian summer monsoon northern marginal zone - Fang, Congxi; Liu, Yu; Song, Huiming; Cai, Qiufang; Liu, Heng; Li, Qiang; Sun, Changfeng (Theoretical and Applied Climatology, 2024)
The northernmost area influenced by the East Asian summer monsoon (EASM) is named the EASM northern marginal zone (ENMZ). The ENMZ is an important area lying in northern and northeastern China with scarce precipitation and a vulnerable environment. However, the existing monsoon indices have weaknesses in characterizing the ENMZ precipitation variability, which limits our ability to understand and forecast local climate changes. In this study, a new index, named the ENMZ index (ENMZI), is proposed to represent the variability in ENMZ summer precipitation. The ENMZI is defined by the meridional shear of 200-hPa zonal wind anomalies, expressing the meridional displacement of the East Asian jet and the trough anomaly over Lake Baikal. The ENMZI serves as a regional monsoon index complementing the existing monsoon indices and representing the variabilities in the EASM northward advance and rainfall over northern and northeastern China. The higher the ENMZI is, the higher latitude the EASM reaches, and the more rainfall the ENMZ has. The physical mechanism for the ENMZI representing the ENMZ precipitation variability is explicated by anomalous vorticity and temperature advection associated with the ENMZI and positive feedback between vertical motion and diabatic heating anomalies. The variability of ENMZI is jointly modulated by variabilities in air-sea coupling modes from the North Atlantic, tropical Pacific, and North Indian Ocean and in atmospheric wave trains over Eurasia. Thus, the ENMZI can be a reliable benchmark for studies in climatically sensitive areas in northern and northeastern China.